Gender and Climate Change in Latin America: An Analysis of Vulnerability, Adaptation and Resilience Based on Household Surveys. (17th October 2016) - Andersen, Lykke E.; Verner, Dorte; Wiebelt, Manfred
Abstract: This paper analyses gender differences in vulnerability and resilience to shocks, including climate change and climate variability, for Peru, Brazil and Mexico, which together account for more than half the population in Latin America. Vulnerability and resilience indicators are measured by a combination of the level of household incomes per capita and the degree of diversification of these incomes. Thus, households which simultaneously have incomes which are below the national poverty line and which are poorly diversified (Diversification Index below 0.5) are classified as highly vulnerable, whereas households which have highly diversified incomes above the poverty line are classified as highly resilient. The analysis shows that female headed households in all three countries tend to be less vulnerable and more resilient than male headed households, despite the fact that the former usually have lower education levels. Copyright © 2016 John Wiley & Sons, Ltd.